TrueColours ulcerative colitis (TCUC): Will patients with UC complete digital questionnaires in real-time? - Walsh, A; Peters, M; Hinds, CM; Kormilitzin, A; Sexton, V; Seeva, P; Brain, AO; Keshav, S; Uhlig, H; Simmons, A; Geddes, JR; Goodwin, G; et al. (Oxford University Press, 2018)
TCUC is a comprehensive real-time web-based programme for UC patients. It monitors multiple parameters via electronic questionnaires: symptoms, quality of life (QoL), and outcomes (eg hospitalisation). Medications are entered and personalised treatment guidance formulated. This information, graphically displayed on a traffic light system, is available to the patient and clinical team via the TCUC website (https://ouh.truecolours.nhs.uk/ibd/en/), and is housed on a secure National Health Service server. The objectives were to assess feasibility, usability and adherence of TCUC.